Is Further Evaluation of Areas with Faint MDP Uptake Needed in Individuals with Oligo-Metastatic Prostatic Adenocarcinoma? - Sharma, Anshul; Dwivedi, Ankur (World Journal of Nuclear Medicine, 2022)
A 42-year-old male patient with high-risk prostate adenocarcinoma underwent baseline 99mTc-methylene diphosphonate skeletal scintigraphy, which revealed two skeletal metastases and an area of faint radiotracer uptake in the left femoral shaft. In view of oligo-metastatic nature of the disease in the bone scan and the young age of the patient, he was a candidate for metastases-directed treatment. Single photon emission computed tomography (SPECT)/CT was performed to further characterize this lesion. It was revealed to be a small soft tissue density lesion within the fatty bone marrow density, suggesting bone marrow involvement. A more sensitive evaluation of such areas with faint radiotracer uptake may be needed in high-risk prostate cancer patients where access to advanced modalities is limited. Their significance will also need reassessment as their detection will improve with technological advancements.
Keywords: high-risk prostate cancer; 99mTc-MDP; skeletal scintigraphy; bone marrow metastasis; oligometastatic disease